2009
DOI: 10.1097/gme.0b013e3181775eb4
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive functioning detrimentally affected after early, induced menopause?

Abstract: Although smaller prospective studies have found that surgical menopause is associated with specific deficits in the memory (visual and verbal) and verbal fluency domains, larger randomized, controlled trials have generally found no effect of surgical menopause on cognitive functioning. The effects of chemical menopause are harder to assess as only three prospective trials have explicitly investigated the effect of induced menopause in the context of breast cancer treatment, and the results remain inconclusive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 50 publications
1
27
2
1
Order By: Relevance
“…These results are consistent with improved memory in mice given other replacement estrogens treatments [52]. Over half of randomized clinical studies find significant improvements in cognition and attention after estrogen replacement therapy (Table 1) [53]. Estradiol has been shown to increase levels of ApoE in the brain, proposed to be beneficial for neuronal reorganization and repair [7].…”
Section: Estradiolsupporting
confidence: 72%
“…These results are consistent with improved memory in mice given other replacement estrogens treatments [52]. Over half of randomized clinical studies find significant improvements in cognition and attention after estrogen replacement therapy (Table 1) [53]. Estradiol has been shown to increase levels of ApoE in the brain, proposed to be beneficial for neuronal reorganization and repair [7].…”
Section: Estradiolsupporting
confidence: 72%
“…The results also showed that . However, it was found no effect of surgical menopause on cognitive functioning 3 . Estrogen replacement therapy has been reported to prevent or delay cognitive decline in postmenopausal women and in estrogen-depleted animals 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that estrogen may prevent cognitive impairments due to aging 2 . Increasing in the risk of Alzheimer's disease due to estrogen deficiency has been reported 3 . It was also found that estrogens have enhancing action on memory tasks 4 .…”
Section: Brain Tissue Oxidative Damage As a Possible Mechanism For Thmentioning
confidence: 99%
“…An earlier age at menopause, 5,6 particularly surgical menopause, [7][8][9] has been associated with increased risk of dementia and cognitive decline in some but not all 10,11 studies. [12][13][14] In general, prior studies of surgical menopause examined the risk of developing Alzheimer disease (AD) or dementia but did not assess intermediate phenotypes, such as change in performance on detailed cognitive testing or development of the neuropathologic features associated with AD.…”
mentioning
confidence: 99%